2022
DOI: 10.1007/s00402-022-04678-w
|View full text |Cite
|
Sign up to set email alerts
|

Did the dislocation risk after primary total hip arthroplasty decrease over time? A meta-analysis across six decades

Abstract: Background While continuous optimization is attempted to decrease the incidence of dislocation after total hip arthroplasty (THA), dislocation remains a major complication. This meta-analysis aims to analyze the evolution of the dislocation risk after primary THA over the decades and to evaluate its potential publication bias. Patients and methods A systematic search was performed according to the PRISMA guidelines for this meta-analysis in the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Great care should be taken when comparing our results with studies from other countries or registries due to the high risk of underreporting. A recently published review employing international cross-country data from the last 6 decades concluded that the yearly dislocation rate had declined to as low as 0.7% between 2010 and 2020 [ 18 ]. Likewise, a large Medicare register study including data from 2010 to 2018 found a low 1-year dislocation risk of 1.6% in patients with OA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Great care should be taken when comparing our results with studies from other countries or registries due to the high risk of underreporting. A recently published review employing international cross-country data from the last 6 decades concluded that the yearly dislocation rate had declined to as low as 0.7% between 2010 and 2020 [ 18 ]. Likewise, a large Medicare register study including data from 2010 to 2018 found a low 1-year dislocation risk of 1.6% in patients with OA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%